O quadrado tensorial não-abeliano, construções relacionadas e p-grupos - Souza, Sofia de Siqueira e (2024)
Let G and Gφ be two isomorphic groups. We study the group ν(G) that is an extension of the non-abelian tensor square of G, G⊗G. We show how ν(G) preserves properties from the group G in question. We also study potent and powerful finite p-groups. We prove that the non-abelian tensor square of G and the k-th term of the lower central series of ν(G) are potently embedded in ν(G), when G is a potent finite p-group. Moreover, for an odd prime p, if G is a potent p-group, then exp(ν(G)) divides p · exp(G)